2022
DOI: 10.1007/s10904-022-02509-4
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Correlation of Modulated Architectures of β-Ag2MoO4 Microcrystals: Effect of Different Synthesis Routes on the Morphology, Optical, Colorimetric, and Photocatalytic Properties

Abstract: In this paper, the effect of different synthesis methods, such as controlled precipitation (CP), sonochemical (SC), hot solution ion injection with fast cooling, and conventional hydrothermal (CH) in obtaining beta-disilver molybdate (β-Ag 2 MoO 4 ) are explained in details. X-ray diffraction patterns, Rietveld refinement data, cluster modeling, micro-Raman, and Fourier transform infrared spectroscopies confirmed that all β-Ag 2 MoO 4 crystals have a spinel-like cubic structure, space group (Fd 3 m), and symme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 91 publications
1
5
0
Order By: Relevance
“…To better comprehend the composite's wear behavior at elevated temperatures, the element distribution and the phase constituents of the worn surface were analyzed by the micro-zone Raman spectrum (Figure 13) and by SEM (with EDS) (Figures 14-16). Results indicate that the main phase constituents are BaMoO 4 , Ag 2 MoO 4 , and NiCr 2 O 4 [39][40][41], and the intensity of these oxides increases as the testing temperature rises from 25 to 800 • C (Figure 13c), which is consistent with the previously reported results. Furthermore, it has been shown that the oxide layer with these constituents can reduce friction and wear effectively in a tribopair system [6,28].…”
Section: Worn Surface Analysissupporting
confidence: 92%
“…To better comprehend the composite's wear behavior at elevated temperatures, the element distribution and the phase constituents of the worn surface were analyzed by the micro-zone Raman spectrum (Figure 13) and by SEM (with EDS) (Figures 14-16). Results indicate that the main phase constituents are BaMoO 4 , Ag 2 MoO 4 , and NiCr 2 O 4 [39][40][41], and the intensity of these oxides increases as the testing temperature rises from 25 to 800 • C (Figure 13c), which is consistent with the previously reported results. Furthermore, it has been shown that the oxide layer with these constituents can reduce friction and wear effectively in a tribopair system [6,28].…”
Section: Worn Surface Analysissupporting
confidence: 92%
“…Comprehending the intricate relationship between the structure, defect nature, and electrical transport properties is paramount in the design of multifunctional semiconductors. Molybdates with the molecular formula X 2 MoO 4 , where X = Li, Tl, and Ag, have garnered significant attention within the scientific community due to their remarkable photocatalytic properties, 1,2 applications in scintillators, 3 sensors, [4][5][6] optical fibers, 7 as well as their outstanding performance in diverse applications such as antibacterial, 8 antifungal, 9 antiviral, 10 tribological, 11 microwave dielectric, 12 and supercapacitor electrode 13 applications. Furthermore, highly pure β-Ag 2 MoO 4 with a spinel-type cubic structure has been synthesized for catalysis applications due to its electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Ag 2 MoO 4 is an interesting semiconductor, with a band gap around 3.30 eV [1,2], depending on the polymorph, and it has recently been attracting a lot of interest for its excellent properties, that can find applications in many fields. It has a high electrical conductivity [3], exhibits photoluminescence [3,4], suggesting a possible use as a sensor, it has been claimed that it could be use as supercapacitor [5], it is an excellent catalyst for many organic reactions [6][7][8], and it has shown good antimicrobial capabilities [2,9,10]. These aspects are also combined with very low toxicity [9] and excellent ease of chemical synthesis [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…It has a high electrical conductivity [3], exhibits photoluminescence [3,4], suggesting a possible use as a sensor, it has been claimed that it could be use as supercapacitor [5], it is an excellent catalyst for many organic reactions [6][7][8], and it has shown good antimicrobial capabilities [2,9,10]. These aspects are also combined with very low toxicity [9] and excellent ease of chemical synthesis [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation